PENGEMBANGAN E-LKPD BERORIENTASI KEARIFAN LOKAL BERBANTUAN LIVEWORKSHEET MAPEL PENDIDIKAN PANCASILA KELAS IV SD GUGUS II KECAMATAN BULELENG - Ni Luh Pramiswari; I Made Ariasa Giri; Putu Yulia Angga Dewi (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The urgency of this research lies in the need to develop relevant and contextual learning media, especially in the context of education oriented towards local wisdom The research aims to develop local wisdom-oriented E-LKPD with the help of Liveworksheet on the subject of community identity in the subject of Pancasila Education grade IV SD in Gugus II Buleleng District. The background of this research is the low motivation and involvement of students in learning Pancasila Education which is still conventional and does not link the material with daily life and local values. The research method used is development research (Research and Development) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Product validity was tested through the validation of material experts, media experts, and linguists, while practicality was tested through questionnaires to teachers and students. The data were analyzed qualitatively and quantitatively to determine the feasibility of the developed E-LKPD. The results showed that this Liveworksheet-assisted local wisdom-oriented E-LKPD was declared valid and practical for use in learning.The E-LKPD was able to increase students' learning motivation, engagement, and understanding of Pancasila Education materials, especially in the aspect of community identity associated with local wisdom values. Obstacles found in the form of limited digital devices and technological literacy in some students and teachers, but can be overcome through training and facility support. Thus, this E-LKPD is recommended as one of the innovative learning media to improve the quality of Pancasila Education learning in elementary schools and can be further developed on other materials or levels.